Quantitative high-throughput analysis of tumor infiltrating lymphocytes in breast cancer - Hayashi, Kumiko; Nogawa, Daichi; Kobayashi, Maki; Asakawa, Ayaka; Ohata, Yae; Kitagawa, Shota; Kubota, Kazuishi; Takahashi, Hisashi; Yamada, Miyuki; Oda, Goshi; Nakagawa, Tsuyoshi; Uetake, Hiroyuki; et al. (Frontiers in Oncology, 2022)
Detailed subsets of tumor infiltrating lymphocytes (TILs) were quantified from breast cancer (BC) tissues and compared among BC subtypes. The TILs of BC tissues from 86 patients were classified using multiplex immunohistochemistry and an artificial intelligence-based analysis system based on T-cell subset markers, immunomodification markers, and the localization of TILs. The levels of CD4/PD1 and CD8/PD1 double-positive stromal TILs were significantly lower in the HER2- BC subtype (p <0.01 and p <0.05, respectively). In triple-negative breast cancer (TNBC), single marker-positive intratumoral TILs did not affect prognosis, however CD4/PDL1, CD8/PD1, and CD8/PDL1 double-positive TILs were significantly associated with TNBC recurrence (p<0.05, p<0.01, and p<0.001, respectively).TIL profiles differed among different breast cancer subtypes, suggesting that the localization of TILs and their tumor-specific subsets influence the BC microenvironment.